Psychological injury rehabilitation lags behind physical rehabilitation: Elite athletes` experiences and support within Chinese context - Qin, H.-H.; Zhang, L.-W.; Schinke, R. J.; Giffin, C. E. (Psychology of Sport and Exercise, 2023)
This qualitative study was focused on two objectives: to explore (a) Chinese elite athletes' perceptions of their rehabilitation experiences after severe acute injuries, and (b) support strategies facilitating their return to competition. We interviewed 10 Chinese elite athletes through a semi-structured interview guide consisting of open questions and requests for information about the participants` injury and rehabilitation experiences. We utilized a reflexive thematic analysis to interpret participants` accounts. Two themes are presented to reveal the Chinese elite athletes` perceptions: (a) psychological injury rehabilitation lags behind physical rehabilitation and (b) post-injury psychological support within the CWNS.This study contributes to athlete rehabilitation scholarship by providing a unique Eastern, collective perspective embedded with the Chinese Whole Nation System (CWNS).